Considering tradeoffs in “local” food policies: examples from school feeding programmes - Jablonski, Becca B. R.; Milbourne, Paul; Maderson, Siobhan; Morgan, Kevin (Frontiers in Nutrition, 2023)
City, national, and multinational governments are increasingly leveraging nutrition programme spending, specifically pursuing policies that require or incentive “local” procurement, to meet a myriad of goals. However, these policies involve tradeoffs that are often not fully considered by government officials, planners, and advocates. This perspective article provides some examples of those tradeoffs from the peer-reviewed literature, which, we argue, are useful to consider in setting school feeding programme policies to achieve sustainability goals.